Experience of Pain Relief in Patients Operated for Cervical Disc and P-Cage Fusion (Medical Forum Monthly, 2024)
ABSTRACTObjective: The purpose of this case series, retrospective study was to assess the effectiveness and results of single-level ACDF using PEEK cage fusion in patients with cervical radiculopathy or myelopathy.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Hayatabad Medical Complex (HMC) in Peshawar. The study spanned a duration of one year, from July 7, 2019, to July 7, 2020.Methods: The present study is a cross-sectional study of 43 patients who had single-level ACDF with PEEK cage fusion during one year at Hayatabad Medical Complex, Peshawar. Patients’ characteristics, the surgery details, and the results were considered. Patients’ pain intensity was assessed using the Visual Analog Scale (VAS) before the operation and one week after the operation. Other aspects measured included the complications that arose and the satisfaction level of the patients.Results: The average age of the surveyed patients was 45 years, of which 79. 09% were men. Postoperative pain management was satisfactory; 90% of the patients experienced a decrease in pain severity. The mean reduction in VAS scores from baseline to one week after surgery was, therefore, -5. 07. No significant differences in pain relief outcomes were observed when performing subgroup analyses according to the patients’ age, gender, and preoperative pain severity. The patients were generally satisfied with the treatment they received and none of the patients experienced any serious side effects in the one-week follow up. The cervical discs that were operated upon were spread out over different levels with the most common level being C5-C6.Conclusion: Single-level ACDF with PEEK cage fusion has shown good results in patients’ satisfaction and mean pain relief. The current work contributes to the existing body of knowledge on the outcomes and complications associated with ACDF with PEEK cage implantation as a management strategy for cervical disc disease. Therefore, longer-term follow-up studies are needed to confirm these findings and evaluate the sustainability of the results.